0441 Treating Insomnia Disorder in Black Women: Results from an Internet-Based, Randomized Clinical Trial of a Culturally Tailored Intervention. (25th May 2022) - Zhou, Eric; Ritterband, Lee; Bethea, Traci; Robles, Yvonne; Heeren, Timothy; Rosenberg, Lynn
Abstract: Introduction: Black women are at high risk for insomnia. Despite considerable interest in addressing sleep health disparities, there is very limited research investigating the efficacy of gold standard treatment (cognitive-behavioral therapy for insomnia; CBT-I) among this minority population. Further, we are not aware of any data studying whether a culturally tailored intervention would improve treatment efficacy and/or engagement among Black women. Methods: We conducted a randomized clinical trial within a national, longitudinal cohort study (Black Women's Health Study; BWHS). BWHS participants with elevated insomnia symptoms were randomized to receive: (1) automated Internet-delivered CBT-I (Sleep Healthy Using the Internet; SHUTi); (2) a stakeholder-informed, tailored version of SHUTi for Black women (SHUTi-BWHS); or (3) patient education about sleep (PE). Primary outcomes were insomnia severity (Insomnia Severity Index; ISI) and treatment engagement (completion of the intervention). We hypothesized that both SHUTi and SHUTi-BWHS would lead to significantly decreased insomnia severity compared to PE, and that SHUTi-BWHS participants would be more likely to complete the intervention. Results: Three-hundred and thirty-three Black women (mean age=59.3 years) were enrolled in the trial. Those randomized to receive either SHUTi or SHUTi-BWHS had greater reductions in ISI scores at 6-month follow-up (-10.0 and -9.3 points, respectively) compared to PE (-3.6 points). More participants randomized to SHUTi-BWHS completed the intervention compared to those randomized to SHUTi (78.2% vs 64.8%; p<.01). Participants who completed either SHUTi or SHUTi-BWHS showed greater reductions in insomnia severity compared to non-completers (-10.4 vs -6.2 points; p<.01). Conclusion: Both SHUTi and SHUTi-BWHS improved sleep outcomes more than an active control. The culturally tailored SHUTi-BWHS program was more effective at engaging participants with the program as a greater proportion completed the full intervention, which was associated with greater improvements in sleep outcomes. These compelling data demonstrate that offering a culturally adapted program is a possible path in efforts to address the sleep health disparities facing Black Americans. Support (If Any): This trial was funded by Patient-Centered Outcomes Research Institute grant AD-2017C1-6314. National Cancer Institute grant U01 CA164974 supports the BWHS infrastructure.